Inversion of Elastic and Fracture Parameters in Tilted Transverse Isotropic Media with Parameter Standardization - Guangzhi Zhang; Shengzhao Dai; Han Li; Hongjian Hao; Tengfei Chen (Applied Sciences)
This study addresses inversion challenges in tilted transverse isotropic (TTI) media affected by inclined fractures. A new method is proposed to derive the reflection coefficient for such media, combining scattering theory with the steady-phase method. To enhance inversion accuracy and stability, a scale normalization technique is introduced. The approach improves parameter consistency during the inversion process. The results highlight the potential of this method to offer valuable technical support for fractured reservoir exploration and development.